ZONE OF INFLUENCE OF INTERNATIONAL TRANSPORT CORRIDORS IN THE ODESSA REGION - Герасименко, Оксана (SWorldJournal, 2023)
The purpose of the publication is to study the state of development of the transport system of the Odessa region in the context of European integration processes. An analysis of transport corridors No. 7 and 9 within the Odessa region was carried out. Its